Effect of Photodynamic Therapy Using Toluidine Blue on Eikenella corrodens and Aggregatibacter actinomycetemcomitans Biofilms Adhered to Titanium Discs: An In Vitro Study - MR Karimi; M Montazeri; M Harandi; L Aghazadeh; L Aghazadeh (Islamic Azad University, 2018)
Background and aim: Antimicrobial photodynamic therapy (aPDT) has been suggested as a novel technique for decontamination of exposed implant surfaces. We aimed to evaluate the effect of aPDT on sandblasted, large-grit, acid-etched (SLA) titanium discs contaminated with Eikenella corrodens (Ec) and Aggregatibacter actinomycetemcomitans (Aa). Materials and methods: In this in-vitro study, twenty-four sterile SLA titanium discs were contaminated with Ec (PTCC® 1391) and Aa )ATCC® 33384( and were randomly divided into the following groups: aPDT-treated group consisted of 12 discs submerged in 1 ml of toluidine blue and exposed to a low-level laser; negative control group comprised of 6 discs rinsed with physiological saline, and positive control group included 6 discs submerged in 2 ml of 0.2% chlorhexidine (CHX). After serial dilution, each sample was cultivated in an anaerobic environment (24 hours for Ec and 48 hours for Aa). Microbial reduction rate was calculated through colony-forming unit (CFU) counting according to Kruskal-Wallis test. Results: The number of colonies for both bacterial strains in the aPDT-treated group was significantly reduced compared to the negative control group, showing the bactericidal potential of aPDT with toluidine blue (P<0.0001). The 0.2% CHX group showed a significantly smaller amount of colonies (CFU=1.089×107 for Ec and 3×107 for Aa) compared to the aPDT-treated group (CFU=3.73±1.19×109 for Ec and 52±13.6×105 for Aa; P<0.00001). Conclusion: aPDT with toluidine blue significantly reduces Ec and Aa contamination of SLA titanium discs; however, 0.2% CHX showed the highest bactericidal potential and is still considered the gold standard in antimicrobial treatment of peri-implant diseases.